2016
DOI: 10.1590/1807-2577.12216
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the dentin changes in teeth subjected to endodontic treatment and photodynamic therapy

Abstract: ResumoIntrodução: A PDT antimicrobiana é um eficiente método coadjuvante na desinfecção do sistema de canais radiculares, o que torna importante o estudo sobre a possibilidade de alterações morfológicas e permeabilidade provocadas pelo laser de diodo na estrutura dentinária radicular. Objetivo: A proposta deste estudo foi investigar as alterações morfológicas e percentual de infiltração apical radicular após o uso do laser diodo. Material e método: Quarenta dentes monorradiculares foram instrumentados pelo sis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
1
1
1
Order By: Relevance
“…In the present study, PAD recorded high smear scores without significant difference with conventional syringe-needle irrigation, this was in disagreement with Lacerda et al [38] , who reported that PAD resulted in reduction of the smear layer and opening of the dentinal tubules. This could be explained by different light parameters and wavelengths (arsenide, gallium, and aluminum laser diode), light delivery technique (insertion of the tip was to the WL) and interaction time of the dye with the medium.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, PAD recorded high smear scores without significant difference with conventional syringe-needle irrigation, this was in disagreement with Lacerda et al [38] , who reported that PAD resulted in reduction of the smear layer and opening of the dentinal tubules. This could be explained by different light parameters and wavelengths (arsenide, gallium, and aluminum laser diode), light delivery technique (insertion of the tip was to the WL) and interaction time of the dye with the medium.…”
Section: Discussioncontrasting
confidence: 99%
“…Debris removal and antibacterial efficiency has therefore been the subject of several in vitro and ex vivo research [12][13][14][15][16][17][18].For evaluating PUI and laser disinfection during root canal irrigation, there is minimal known evidence for postoperative discomfort in a single visit endodontic therapy. Therefore, the null hypothesis used in the design of this study was that there was no difference between postoperative pain or discomfort or both during root canal treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Portanto, novas técnicas e novos métodos estão sendo utilizados com objetivo de minimizar as taxas de insucesso. Com a finalidade de melhorar o tratamento convencional, a terapia fotodinâmica associada ao laser apresenta-se como alternativa coadjuvante na eliminação dos microrganismos 1,2 .…”
Section: Introductionunclassified